A Mapped Locus on LG A6 of Brassica juncea Line Tumida Conferring Resistance to White Rust Contains a CNL Type R Gene - Bhayana, Latika; Paritosh, Kumar; Arora, Heena; Yadava, Satish Kumar; Singh, Priyansha; Nandan, Divakar; Mukhopadhyay, Arundhati; Gupta, Vibha; Pradhan, Akshay Kumar; Pental, Deepak (Frontiers in Plant Science, 2020)
White rust, causal agent oomycete Albugo candida, is a significant disease of the cultivated Brassica species. The Indian gene pool lines of oilseed mustard, Brassica juncea, are highly susceptible to the pathogen. Resistance to A. candida has been reported in the east European gene pool lines of mustard and mapped to LG A4 in line Heera and LG A5 in line Donskaja-IV. A new resistance-conferring locus to A. candida isolate AcB1 has been mapped to LG A6 of B. juncea line Tumida ̶ a Chinese vegetable type mustard using an F1DH mapping population that has been developed from a Tumida × Varuna (susceptible Indian gene pool line) cross. A molecular map containing 8303 genic and GBS markers was used to map the resistance trait to an interval of 63.0 cM ̶ 70.8 cM on LG A6. Genome assemblies of Tumida and Varuna were used to find the genes present within the flanking markers discerned by genetic mapping. The most likely candidate gene in the mapped interval is BjuA046215, a CC-NBS-LRR (CNL) type R gene that encodes a protein with all the specific subdomains of the proteins encoded by such genes. Alleles of BjuA046215 in Varuna and other lines of the Indian and the east European gene pools encode proteins that have truncated LRR domains. Analysis of the syntenic regions in some of the Brassicaceae genomes and phylogenetic analysis of CNL type R genes showed BjuA046215 to be closely related to a recently described white rust resistance-conferring R gene BjuWRR1 in B. juncea Donskaja-IV, both belonging to the CNL-D group of R genes. Related R genes in Arabidopsis thaliana confer resistance to another oomycete, Peronospora parasitica.